2017
DOI: 10.1016/j.jdent.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oral health and oral health related quality of life among elderly people in United Kingdom

Abstract: Whereas previous research has suggested a moderate relationship between oral disease and quality of life in this large scale survey of older adults, the presence of active caries and the presence of one or more of the PUFA indicators are associated with impaired oral health related quality of life in older adults, but not indicators of periodontal status. The implication of this is that whilst focussing on prevention of disease, there is an ongoing need for oral health screening and treatment in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
133
5
25

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 20 publications
23
133
5
25
Order By: Relevance
“…Oral health influences psychological health, well‐being and life satisfaction (Christensen, Hede, & Nielsen ; Gil‐Montoya, Ferreira de Mello, Barrios, Gonzalez‐Moles, & Bravo ; Kisely ; Locker, Clarke, & Payne ; Masood, Newton, Bakri, Khalid, & Masood ; Persson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health influences psychological health, well‐being and life satisfaction (Christensen, Hede, & Nielsen ; Gil‐Montoya, Ferreira de Mello, Barrios, Gonzalez‐Moles, & Bravo ; Kisely ; Locker, Clarke, & Payne ; Masood, Newton, Bakri, Khalid, & Masood ; Persson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This was the first rapid review of the oral health of EOL patients from a dental perspective. This is a surprising finding given that, first, the aim of palliative care is often cited as “to maintain quality of life”, and second, that the link between oral health and quality of life has been well established . One review examined oral health in this population; however, it was limited to studies from a nursing perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization in 2012 in Galloway suggests that the correlation between oral health-related quality of life (OHRQoL) and well-being was influenced by six factors; physical, environment, social relationships, physiological, independence stage and spiritual life. The result of the empirical analysis suggested that the impact of the quality of life relates to social demographic data (age and gender) along with economic and epidemiological aspects of culture [1, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%